The study of intersecting strokes made with the ink of roller pens, laser printer toner, and stamp ink of the print impression - Sadykov, М.А.; Sakupova, М.О.; Altaev, Е.А. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2023)
The authors raise the question of solving the relative prescription of the document by examining the intersecting strokes of the requisites. The relevance of the above topic is presented in the article. Also, the relevance increases as the properties of writing instruments and the chemical composition of coloring substances in strokes change. It is noted that the absence of a dispute or discussion on this topic in scientific circles has a negative impact not only on the development of theoretical positions but also does not allow experts to solve in practice the issues of the chronological sequence of the execution of the requisites of documents submitted for examination or research. The methods and methods developed earlier and tested in long-term forensic practice are indicated. Step-by-step instructions for the expert's work are recommended: inspection of a document indicating the presence of intersecting strokes, conducting thin-layer chromatography to establish the chemical composition of materials, studying the properties of strokes using a microscope, using a spectral microscope to study invisible spectral zones, preparing and copying strokes on an adsorbent moistened with water or solvents. Attention is drawn to such an important aspect during the experimental stage of copying as the correct selection of adsorbent, humidifiers (water, solvents), and contact time. The presented article is written on the basis of an information letter approved at a joint meeting of the Scientific and Methodological Council of the NIISE of the Ministry of Education and Science of the Republic of Kazakhstan.